TABARRUJ: SAYYID QUTHB'S PERSPECTIVE IN TAFSIR FI ZHILAL AL-QUR’AN - Murni, Murni; M., M. Ghalib; Mahfudz, Muhsin; Firdauz, Firdauz (Ridwan Institute, 2024)
This study focuses on the concept of Tabarruj as interpreted by Sayyid Quthb in his Tafsir fi Zhilal al-Qur’an. The research explores the essence, existence, and impact of Tabarruj from Quthb's perspective, offering an in-depth analysis of how this concept is related to faith, social behavior, and gender roles in Islam. The essence of Tabarruj is linked to the weakening of faith and human morality, influenced by destructive social environments, and the fading of one's spiritual essence. Its existence manifests in specific behaviors, particularly among women, such as leaving the house without necessity, excessive social interaction with men, flirtatious behavior, and immodest dress. The study identifies significant impacts of Tabarruj, including the rise of social ills, the erosion of women's dignity, and the diminishing blessings of Allah in human life. The research contributes to the scholarly understanding of Islamic teachings on modesty, faith, and gender by examining Quthb’s interpretation of Tabarruj and its relevance to contemporary issues. Future research could compare Quthb’s views on Tabarruj with modern interpretations of modesty across different cultural and historical contexts, as well as examine the influence of digital and social media on the concept of Tabarruj among younger generations in Muslim societies.